Analisa Percepatan Keterlambatan Proyek (Study Kasus : Kantor Dinas SKPD Pemko Gedung B2 Di Tenayan Raya) - Lidwyna, Finsensia; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Planning and project scheduling always refer to assumptions and forecasting and schedule planning.Problem will occure if there discrepancies between planning and actual. Delay of project implementation will make economies consequencies for owner and contractor. Problem and conflict will arise when there are argument between owner and contractor come along with time and cost additive. The project of governmental office building in Pekanbaru City experienced of 75 days delay. To overcome this problem, there were 3 solutions. First, by using overtime work, second, adding worker and equipment, third, is shift. The analysis focused on the critical path. As a results, the cost of SKPD B2 building construction delay was calculated as Rp. 4.497.790.458,25. The acceleration cost was Rp.2.280.496.543,31 with a total 11690 hours of extra work for workers and 156 hours for total station for overtime work alternative, Rp. 2.719.277.132,05 with 14 workers and 2 equipment on night shift for the addition of workers and equipments alternative, and Rp. 2.719.277.132,05 with 14 workers and 2 units of equipment during the night shift time-shift work alternative. The best acceleration method or alternative was the overtime work method which was timely and its efficiency was 49%.Keywords: Construction delay, construction cost, SKPD B2 Building, overtime, addition of workers and equipments, time-shift work